STUDI BEBAN PENCEMARAN LOGAM BERAT KADMIUM (Cd) PADA BALLAST WATER KAPAL BARANG DAN KAPAL PENUMPANG DI PELABUHAN TANJUNG EMAS SEMARANG - Anugrah Febrino Balwa; Nurjazuli Nurjazuli; Tri Joko (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Ballast water exchange is one of the operations of the ship. The more number of vessels that lean to make the amount of ballast water that is dumped in the waters of the port of Tanjung Emas the more higher. Ballast water pollution due to the cargo and passenger ships at the Port of Tanjung Emas cause pollution load which impact indirectly on the quality of water.The purpose of this study was to determine the burden of the heavy metal cadmium pollution of water ballast cargo and passenger ships in the Port of Tanjung Emas in Semarang.This type of research is descriptive survey with cross sectional approach. The variables in this research include the number of vessels, the type of ship, age of ship, cadmium levels ship ballast water, sewage discharge ballast water of ships and ship ballast water pollutant load. Population and sample in this research were 30 cargo and passenger ships with criteria that ship rely at the port of Tanjung Emas in Semarang and have a ballast water tank. The results showed cadmium levels of 30 samples ship ballast water (100%) is above the threshold value with the highest level of 2,457 mg/l and the lowest level of 1,076 mg/l. Waste discharge ballast water ships at the Port of Tanjung Emas highest level of 350 m3/hour and the lowest level of 1.00 m3/hour. The results of pollutant load calculations ship ballast water of 30 samples cargo and passenger ships at the Port of Tanjung Emas shows that the highest pollutant load of 0,782 kg/day and most lower pollutant load 0,002 kg/day. The conclusion of this study is the pollutant load of cadmium from the cargo and passenger ships at the Port of Tanjung Emas has a varies value depending on the type of ship and vessel age.